Strategi Penetapan Harga untuk Layanan di Era Modern (Pricing Strategy for Services in The Modern Era) - Sinarwaty; Enjelita Enjelita; Dewi Amor (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid growth of the service sector amid business competition and digital transformation requires companies to develop effective and adaptive pricing strategies. The main problem addressed in this study is the complexity of service pricing, which is influenced by the unique characteristics of services such as intangibility, heterogeneity, perishability, and the high dependence of customers on perceived value. These conditions require companies to balance competitive pricing, customer value, and profitability goals. The research problems in this study are: (1) how the main concepts and approaches of service pricing strategies are applied in modern companies, and (2) what factors influence the successful implementation of service pricing strategies in enhancing customer value and satisfaction. This study aims to analyze service pricing strategies comprehensively, identify the factors affecting their effectiveness, and provide systematic insights as academic and practical references. The findings indicate that modern service pricing strategies focus not only on cost-based approaches but also on value- based pricing, price differentiation, dynamic pricing, and integration with customer relationship strategies. The success of pricing strategies is influenced by the alignment between price and perceived value, customer segmentation, service quality, price transparency, market competition, pricing flexibility, the use of technology, and the development of long-term customer relationships.